Al-Qur’ān dan Reproduksi Perempuan dalam Perspektif Aktivis Gender Indonesia (Analisis Tafsir Nur Rofi’ah) - Aisyah Aisyah; Kurdi Fadal (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2021)
Women naturally experience five biological experiences of women in the form of menstruation, pregnancy, childbirth, postpartum, and breastfeeding. Reproductive function is often found with pain, exhaustion, and risk. Nur Rofi'ah is here to present an interpretation of the reproduction verse by looking at the reality of society, especially the reality experienced by women. This research method is a type of qualitative research in the form of library research and the sociology of knowledge approach. The method of collecting data is by digging directly from studies of the KGI (Islamic Gender Justice) Koran and related literature and presenting data from the medical and psychological side of the condition of women experiencing reproductive function. From the author's analysis, it is concluded that Nur Rofi'ah's interpretation is part of the paradigm of transformative interpretation of reproductive verses. His explanation of the word aÅ¼a which means pain becomes a reconstruction of the meaning of the verse while in explaining the words wahnÄn'alÄ wahnin and kurhÄn, he reproduces the meaning of the verse on the previous interpretations by providing an explanation of the condition of women who are menstruating, pregnant, giving birth, postpartum, and breastfeeding. From a medical and psychological perspective, the interpretation is expected to be a change in the attitude of the environment, family, especially husbands to be more caring and sympathetic.